eCM 2011
DOI: 10.22203/ecm.v022a30
|View full text |Cite
|
Sign up to set email alerts
|

Efficient animal-serum free 3D cultivation method for adult human neural crest-derived stem cell therapeutics

Abstract: Due to their broad differentiation potential and their persistence into adulthood, human neural crest-derived stem cells (NCSCs) harbour great potential for autologous cellular therapies, which include the treatment of neurodegenerative diseases and replacement of complex tissues containing various cell types, as in the case of musculoskeletal injuries. The use of serum-free approaches often results in insuffi cient proliferation of stem cells and foetal calf serum implicates the use of xenogenic medium compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 59 publications
5
77
0
Order By: Relevance
“…Although it is clear that cells residing in the subepithelial soft tissue of the palate can achieve bone regeneration, this population is heterogenous (Harris, 1999), but it is not known which subpopulations are capable of achieving regeneration. Indeed, cells derived from palate were found to have specific properties, such as increased proliferation rates, and representative of a regenerative phenotype as shown by research group (Greiner et al 2011, Widera et al 2009). …”
Section: Introductionmentioning
confidence: 77%
“…Although it is clear that cells residing in the subepithelial soft tissue of the palate can achieve bone regeneration, this population is heterogenous (Harris, 1999), but it is not known which subpopulations are capable of achieving regeneration. Indeed, cells derived from palate were found to have specific properties, such as increased proliferation rates, and representative of a regenerative phenotype as shown by research group (Greiner et al 2011, Widera et al 2009). …”
Section: Introductionmentioning
confidence: 77%
“…For example, one study demonstrated that palatal tissue-derived stem cells in the subepithelial soft tissue of the palate could be used in bone regeneration [Harris, 1999]. Other research showed that stem cells derived from palatal tissue had specific properties, such as increased proliferation rates and a regenerative phenotype [Widera et al, 2009;Greiner et al, 2011]. Roman et al [2013] were the first to identify palatal tissue-derived MSCs and named them progenitor-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…At a confluency of approximately 80%, osteogenic induction medium was applied containing DMEM, 10% FCS, 100 nM dexamethasone (Sigma-Aldrich, St. Louis, USA), 10 mM β -glycerophosphate (Sigma-Aldrich, St. Louis, USA) and 0.05 mM L-ascorbic acid-2-phosphate (Sigma-Aldrich, St. Louis, USA) at 37 °C and 5% CO 2 in a humidified incubator as described by Greiner et al 21. Control cells were cultured in DMEM supplemented with 10% FCS.…”
Section: Methodsmentioning
confidence: 99%
“…Inferior turbinate stem cells (ITSCs) are routinely isolated during minimally-invasive surgery20 and can easily be expanded in vitro 21 under clinical-grade conditions22. In vitro , ITSCs revealed an extraordinarily broad differentiation potential into ectodermal as well as mesodermal cell types212324.…”
mentioning
confidence: 99%